THE DIFFERENTIATION OF SETTLEMENTS IN THE MUNICIPALITY OF SREBRENICA AS A CONSEQUENCE OF AGGRESSION - Nezirovic, Senada (International Journal of Research -GRANTHAALAYAH, 2024)
The municipality of Srebrenica is located in the northeast of Bosnia and Herzegovina. Due to the aggression, in April 1992, a large number of residents left the area. Thus, the exile crisis of the population of Srebrenica has begun and has not ended to this day. The paper presents theoretical and practical research on the settlements and population of Srebrenica and the changes that occurred after the aggression and genocide. The paper identified the causes and problems faced by the population living in this area today. Apart from literature and planning documents, indicators obtained from municipal departments for social activities, statistical indicators of the Agency for Statistics from the population and household census were used in the preparation of the work. The results show the demographic uncertainty, i.e. the municipality of Srebrenica is, from a demographic point of view, one of the most affected areas by the war in Bosnia and Herzegovina.